MARKET AND SUSTAINABILITY OF FOOD PACKAGING: A REVIEW - Oliveira, Ana Sílvia Boroni de; Melo, Nathália Ramos de (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2019)
Food packaging is an essential tool in the food industry for protecting products from environmental interference that may be detrimental to the product and to the consumers’ health. As a result, the global packaging market is growing and stimulates the development of new technologies to meet the industrial demand. However, with the growth of the production and use of materials from fossil sources, as well as the lack of adequate programs for post-consumer waste management, there has been a deliberate disposal of these materials into the environment, resulting in ecological impacts and health consequences. In this sense, renewable sources have gained prominence and biologically originated materials are one of the main alternatives for new applications in packaging.